Horizontal jump asymmetries are associated with reduced range of motion and vertical jump performance in female soccer players - Roso-Moliner, A.; Lozano, D.; Nobari, H.; Bishop, C.; Carton-Llorente, A.; Mainer-Pardos, E. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Performance in jumping and change of direction tests are good proxies to reflect the skill level during soccer-specific actions. Greater inter-leg asymmetries have been identified as a risk factor for developing acute and overuse injuries and jeopardizing soccer performance. The aim of this study was to assess the association between asymmetry in the unilateral vertical and horizontal jump tests, ankle range of motion, linear velocity, and change of direction in a sample of highly trained adult female soccer players.